Human factor intervention and ergonomic conditions at dressmaking sector industries from industrial design (2020)
The contributions that industrial design offers to multiple business sectors include the intervention of ergonomic factor that favors the optimum conditions for the people in working environments. In this way, the experience and executed actions from a design professional is showed, who from proyectual methodology and investigative action consolidates a set of solutions for two regional companies of dressmaking sector, to articulate new strengths inside their productive logic at the same time that educates the businessmen about the advantages of introducing creative and innovative thinking of design in favor of the industry and generation of applied knowledge.